Prevalence of Malocclusion During Puberty Growth Spurt in Grade X Students of SMA Seven at Gunung Samarinda Health Center - Helti Purwanti; Nafira Junaedi; Risanti Maulidya Luftiana; Akhmad Dzikri; Ratih Wirapuspita Wisnuwardhani (Syntax Corporation Indonesia, 2024)
Malocclusion is anabnormal position of the jaw or teeth. Malocclusion ranges in severity from low to high, reflecting biological differences across individuals. Human growth and development varies, including bone growth during the accelerated growth period during puberty. Individual identification of the pubertal growth spurt period is very important in orthodontic treatment, because the best growth changes are achieved during the pubertal growth spurt.Purpose: This Study aimed to describe the prevalence of Malocclusion in Pubertal growth Spurt at class 10 students of 7 Senior High School during networking at Gunung Samarinda Community Health Center, Balikpapan East Kalimantan.Methods: A descriptive observational study with a crosssectional design was conducted. There were 1339 students recruited in the screening session.